Practice patterns and outcomes of repository corticotropin injection (Acthar® Gel) use in childhood nephrotic syndrome: A study of the North American Pediatric Renal Trials and collaborative studies and the Pediatric Nephrology Research Consortium - Faizan, Mohammed K; McCracken, Courtney; Lieberman, Kenneth; Benfield, Mark R; Leong, Traci (Journal of Clinical Nephrology, 2021)
Objective: We set up a U.S. registry to examine prescription patterns and patient outcomes of repository corticotropin injection (Acthar® Gel) for childhood nephrotic syndrome. Methods: 18 participating U.S. pediatric centers performed retrospective review and prospective observation of patients < 21 years old with nephrotic syndrome treated with Acthar Gel. We captured baseline characteristics, drug regimen and duration, and disease response following treatment. Results: 46 patients, enrolled from 2015 to 2020 were included. 27 (58.7%) were male. 18 patients (39.1%) had a diagnosis of minimal change followed by focal segmental glomerulosclerosis in 16 patients (34.7%). Median age at start of treatment was 12.5 years (IQR 8.5-17.4) compared to 5.3 years at diagnosis (IQR 2.7-10.5 years). 52% were resistant to corticosteroids. The most common Acthar Gel regimen was 80IU twice a week with a median duration of 199 days (IQR 88-365). Among 37 patients with active disease, 18 (49%) were able to achieve partial or complete remission, though all patients that had a positive response were on other immunosuppressants concomitantly. Conclusion: We report the findings of the largest registry cohort of pediatric patients in the U.S. treated with Acthar Gel for clinically challenging cases of nephrotic syndrome. Acthar Gel was successful in inducing remission in approximately half of the patients with active disease at time of treatment. No predictors of response with respect to demographic data, age at start of Acthar Gel therapy, etiology of nephrotic syndrome, presence or absence of comorbidities, or steroid responsiveness was noted.